Career reorientation during the Covid-19 pandemic: Evidence from fresh graduates of Indonesian colleges - Nurus Sa’adah; Vita Fitria; Rr Siti Kurnia Widiastuti (Journal of Social Studies (JSS), 2023)
This research aims to examine the impact of the COVID-19 pandemic on the career reorientation of fresh graduates at Indonesian universities. This study is necessary to determine the changes in attitudes and perceptions of recent graduates as they seek employment, as measured by indicators of psychological quality, gender, and spiritual level. Three Focus Group Discussion meetings were held to achieve the best results, and questionnaires were distributed to 85 resource people. Furthermore, an interpretive analysis model was used to describe the differences in job attainment experienced by respondents before, during, and after the COVID-19 pandemic. According to the study's findings, several changes occurred in the career orientation of fresh graduates from various universities in Indonesia before, during, and after COVID-19. Before the COVID-19 pandemic, fresh graduates had a strong career orientation, as evidenced by their high absorption of job opportunities. Unlike the results of the COVID-19 pandemic, the impact of COVID-19 on new graduates' careers is significant, affecting mental and physical health as well as social interactions.Keywords: Career reorientation; Fresh Graduates; Higher Education; Human Resources; COVID-19